Does Survey Angling CPUE Reflect Population Density of Northern Pike Esox lucius in Small Boreal Lakes? - Turunen, Aatu; Tiainen, Joni; Olin, Mikko; Vainikka, Anssi (Wiley-Blackwell, 2026)
Knowing the relationship between catch per unit effort (CPUE) and population density is crucial for the management of recreational fisheries. We conducted standardized angling for pike in 16 lakes (3.4–22.1 ha) to test whether lure type, color, and pike density affect CPUE and the size of captured fish. Angling CPUE (fish h−1 km−1) was statistically significantly related to pike density (fish ha−1), despite the high variation and uncertainty in CPUE estimates. Lure type affected CPUE, whereas water temperature, use of a boat, time of day, and transect fishability had no effect. CPUE was higher when using spoons compared to spinnerbaits, but lure color (fluorescent vs. natural) had no effect. The length of captured fish was not dependent on lure type or color. Our results suggest that a predefined protocol may help reduce variation in CPUE data; however, it does not yet allow for reliable estimation of pike density.
Keywords: fish stocks; population density; recreational fisheries